2014
DOI: 10.1016/j.pmrj.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Efficacy of Sacroiliac Joint Corticosteroid Injection Based on Arthrographic Contrast Patterns

Abstract: Objective To determine the relationship between sacroiliac joint (SIJ) contrast dispersal patterns during SIJ corticosteroid injection and pain relief at 2 and 8 weeks after the procedure. The association between the number of positive provocative SIJ physical examination maneuvers (minimum of one in all patients undergoing SIJ injection) and the patient’s response to the intervention was also assessed. Design Retrospective chart review. Setting Academic outpatient musculoskeletal practice. Patients Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…One article compared patients’ pain relief with contrast media flow during SIJ . This study showed no differences in pain scores at 2 months between patients when the contrast medium reached the superior aspect of the joint or when there was poor cephalad spread of contrast medium.…”
Section: Resultsmentioning
confidence: 99%
“…One article compared patients’ pain relief with contrast media flow during SIJ . This study showed no differences in pain scores at 2 months between patients when the contrast medium reached the superior aspect of the joint or when there was poor cephalad spread of contrast medium.…”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids may be administered through the intra-articular route to decrease the intensity and duration of pain [19]. Scholten et al [20] confirmed that fluoroscopically guided corticosteroid injections, based on arthrographic contrast patterns, into the superior portion of SIJ were effective in de- for LBP, this study did not find any statistically significant difference in the mean BMI between the discharged and transferred groups. These findings could be attributed to the small sample size which was used in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Scholten and colleagues found that patients with cephalad extension of contrast flow patterns during SIJ injections demonstrated improved pain scores at 2 weeks as compared to patients who had poor cephalad extension. However, there were no significant intergroup differences in pain outcomes at 8 weeks, with both groups improving significantly compared to preinjection baseline pain scores …”
Section: Summary Of the Published Literaturementioning
confidence: 75%
“…However, there were no significant intergroup differences in pain outcomes at 8 weeks, with both groups improving significantly compared to preinjection baseline pain scores. 26…”
Section: Joint Access Techniquementioning
confidence: 99%